Improved energy storage property in polyvinylidene fluoride‐based multilayered composite regulated by oriented carbon nanotube@SiO2 nanowires. Issue 1 (2nd March 2023) - Zhang, Na; Zhao, Hang; Zhang, Chuying; Gao, Shuyan; Zhu, Tongguang; Bai, Jinbo
Abstract: High‐performance dielectric capacitors are essential components of advanced electronic and pulsed power systems for energy storage. Because of their high breakdown strength and excellent flexibility, polymer‐based capacitors are regarded as auspicious energy storage material. However, the energy storage capacity of polymer‐based capacitors is severely limited due to their low polarisation and low dielectric permittivity. The modified Stöber method was used to construct two types of CNT@SiO2 (CS) one‐dimensional core‐shell structured nanowires with different shell thicknesses. By integrating the procedures of solution mixing, melt blending, hot‐stretching orientation and hot pressing, sandwich‐structured poly (vinylidene fluoride) (PVDF)‐based composites were fabricated. The CS core‐shell nanowires dispersed in the inter‐layer serve as electron donors, leading to a high permittivity, while two PVDF outer layers provide the favourable overall breakdown strength. The insulating SiO2 shell can effectively limit the migration of carriers and keep the dielectric loss at a relatively low level in the composites. The CS/PVDF composite exhibited an enhanced discharged density ( 6.1 J/cm 3 ) and breakdown strength ( 241 kV/mm) when the interlayer filled with as small as 1 wt% CS nanowires with the SiO2 shell thickness of 8 nm, which is 203% and 18.7 % higher than pure PVDF ( 2.01 J/cm 3 at 203 kV/mm), respectively. This research presents a practical strategy for designing and fabricating advanced polymer film capacitor energy storage devices.